Pengaruh Pengungkapan Tanggung Jawab Sosial terhadap Manajemen Laba - Eko Budi Santoso (Jurnal Bisnis dan Keuangan, 2021)
This study is based on the paradox where companies that are active in carrying out social responsibility turn out to be involved in financial scandals. The aim of this study is to examine the association of corporate social responsibility (CSR) disclosure with earnings management. This research was conducted at Indonesian go public companies which have issued CSR disclosures according to GRI-G4 for the period of 2013-2017. The result of the study shows that there is positive association of CSR disclosure with earnings management. The findings of this study suggest stakeholders should not take for granted that CSR disclosure of the company automatically reflects their ethical behavior in financial areas.